On the standardization of the fishing effort - LIMA,Álvaro Carvalho de (2000)
In this note we demonstrate that the use of an index to standardize the fishing effort using the cpue of a standard vessel or gear is mistaken, once the cpues- catch per unit of total effort after standardization is similar to cpues - catch per unit of effort of the standard vesel or gear arbitrarily chosen.